2020
DOI: 10.30650/jik.v8i1.1268
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Leprosy Type and Grade of Disability in Leprosy Patients in Samarinda

Abstract: Leprosy or Hansen’s disease is a disease caused by obligate bacteria, Mycobacterium leprae. This disease is a chronic infectious disease with the first affinity in the peripheral nerves. The worst complication of this disease is disability and causes sufferers to be excluded from their social activities. There are several factors that play a role in the occurrence of leprosy defects, one of them is the type of leprosy. This research aims to determine the correlation between the type of leprosy and the grade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…The most common complaint of G1D is loss of sensation (anesthesia) in the hands or feet. 8 Tropical ulcers were the most frequent deformity found in the study by Mangala in 2015-2018, as many as 37,6%. 4 Similar to our study, the most common deformity was an ulcer, found in 95 patients (34.5%).…”
Section: Discussionmentioning
confidence: 83%
“…The most common complaint of G1D is loss of sensation (anesthesia) in the hands or feet. 8 Tropical ulcers were the most frequent deformity found in the study by Mangala in 2015-2018, as many as 37,6%. 4 Similar to our study, the most common deformity was an ulcer, found in 95 patients (34.5%).…”
Section: Discussionmentioning
confidence: 83%
“…Bungin's 2019 research in Samarinda showed that the most frequent complaint in patients with grade-2 disability was the presence of foot ulcers. 6 Tropical ulcers were the most frequent deformity found in the study by Mangala in 2015-2018 as many as 37.6%. 5 An increased incidence of plantar ulcers is repeated trauma in the majority of cases with anesthesia of the foot.…”
Section: Discussionmentioning
confidence: 85%
“…Grade 0 indicates normal sensation with no visible impairments; Grade 1 indicates impaired sensation with no visible impairments; Grade 2 indicates visible impairments/deformity (Eye = lagophtalmos, ectropion, trichiasis, corneal opacity, and visual impairment ; hands = ulcerations, resorption, claw hand, fallen hand ; feet = trophic, resorption, claw foot, drop foot, ankle contracture). 14,15 Grade 1 assessment is really important. Because patients must have passed through the Grade 1 stage prior to entering Grade 2.…”
Section: Discussionmentioning
confidence: 99%